Promoting Inclusivity in Blood Donation: Public Health - Saurabh R Shrivastava; Priyanka Meshram; Swapnil Inkane (National Journal of Community Medicine)
The practice of blood donation supports community unity, as it brings all individuals on a common platform where they help each other and the health system in the mission to save human lives. Regardless of the wide scope and merits of blood donation in saving lives and improving health, it is a fact that many patients who are in need do not receive safe blood timely. As the existing pool of donors cannot meet the requirements of everyone, it is the need of the hour to appeal to and encourage a diverse group of blood donors to support the healthcare delivery system. Acknowledging the need to have a diverse pool of donors, we must promote inclusivity in blood donation and this will require a combination of multiple strategies. In conclusion, the availability of a diverse blood donor base makes it extremely useful for patients from different backgrounds by making the entire process compatible and safe. Many barriers have been identified that could limit the inclusivity in blood donation, and this will require a comprehensive approach to ensure that all communities are equally represented in the donor pool, ultimately leading to a more diverse and adequate blood supply.